The Role of E-trust, Experiential Marketing and Advertising in Purchasing Decision on E-commerce Tokopedia - Icha Vallyncia Rahma; Mashita Fahmi Wardhani; Diana Aqmala; Guruh Taufan Hariyadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Purchasing decisions are the process that consumers do when choosing and buying products or services. This study aims to analyze the factors that influence purchasing decisions on Tokopedia e-commerce, focusing on e-trust, experiential marketing, and advertising. The purpose of this study is to determine how E-trust, Experiential Marketing and Advertising can play a role in purchasing decisions. The study used a quantitative approach involving 107 respondents selected through purposive sampling. The results showed that e-trust did not have a significant effect on purchasing decisions on Tokopedia. This indicates that the electronic trust factor does not have a direct impact on consumer decisions on this platform. In contrast, experiential marketing and advertising have been shown to have a positive and significant effect on purchasing decisions. The experience provided to consumers through interesting interactions and effective advertising can increase consumer interest in buying products. These findings indicate that although e-trust does not have much influence, good consumer experience and appropriate promotion through advertising can be key factors in driving purchasing decisions on Tokopedia. This study provides important insights for e-commerce managers to design more effective marketing strategies.